Web 2.0 applications' usage and trends in top US academic libraries. Issue 1 (11th March 2014) - Boateng, Frank; Quan Liu, Yan
Abstract : Purpose: – This paper aims to explore Web 2.0 technologies usage and trends in the top 100 US academic libraries as exemplified through the academic library websites. Design/methodology/approach: – The top 100 universities were selected from the US News & World Report's (USNWR) 2013 ranked list's top 100 of the best colleges in the USA. Content analysis was used in terms of quantitative approach. A checklist was developed as the main research instrument based on other checklists and questionnaires. Each of the selected university library websites was visited within a period of two weeks to explore implementation and usage of web tools, including SNS, blog, RSS, wikis, podcast/vodcast, and social bookmarking/tagging. Findings: – All 100 academic libraries had a social media presence on Facebook and Twitter, making SNS the most widely applied Web 2.0 tool. The wiki was the least applied Web 2.0 technology, with a 34 percent participation rate. Blog was the second most popular tool with a 99 percent participation rate, followed by RSS and IM/Chat with 97 percent and 91 percent respectively. The vodcast and podcast had 47 percent and 46 percent participation rates respectively, while social bookmarking/tagging were also used by 39 percent of the academic libraries. Research limitations/implications: – This study is completely based on publicly available data regarding usage of Web 2.0 applications. Web 2.0 tools used on library intranets were not analyzed for this study. Outcomes suggest that academic libraries are increasingly using Web 2.0 applications to promote themselves, enhance library services, and highlight resources to patrons. Originality/value: – This is the first research that draws an overall picture of the usage and trends of Web 2.0 applications in the top 100 US academic libraries. This study demonstrates some noticeable patterns regarding usage, trends, and adoption which are relevant to how Web 2.0 applications are perceived and used within academic libraries. The study provides academic libraries with helpful information to better meet their user needs by effectively applying Web 2.0. Additionally, library managers, librarians and other libraries may also find this research beneficial as they plan to deploy Web 2.0.